2013
DOI: 10.1097/aln.0b013e31829bd9e2
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Kilohertz-frequency Spinal Cord Stimulation Produces Intensity- and Frequency-dependent Inhibition of Mechanical Hypersensitivity in a Rat Model of Neuropathic Pain

Abstract: Background Spinal cord stimulation (SCS) is a useful neuromodulatory technique for treatment of certain neuropathic pain conditions. However, the optimal stimulation parameters remain unclear. Methods In rats after L5 spinal nerve ligation, we compared the inhibitory effects on mechanical hypersensitivity from bipolar SCS of different intensities (20%, 40%, 80% motor threshold) and frequencies (50-Hz, 1-kHz, and 10-kHz). We then compared the effects of 1-kHz and 50-Hz dorsal column stimulation at high and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
221
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(239 citation statements)
references
References 43 publications
13
221
3
1
Order By: Relevance
“…Others have shown that 1 kHz can be effective 16, 17, 18, 19. These results are consistent with preclinical studies showing that 1 and 10 kHz are approximately equally effective in reducing the mechanical hypersensitivity associated with neuropathic pain 20, 21, and that frequencies from 2 to 100 kHz all suppressed wide dynamic range (WDR) neuronal activity 22.…”
Section: Introductionsupporting
confidence: 89%
“…Others have shown that 1 kHz can be effective 16, 17, 18, 19. These results are consistent with preclinical studies showing that 1 and 10 kHz are approximately equally effective in reducing the mechanical hypersensitivity associated with neuropathic pain 20, 21, and that frequencies from 2 to 100 kHz all suppressed wide dynamic range (WDR) neuronal activity 22.…”
Section: Introductionsupporting
confidence: 89%
“…Research by Shechter et al [5] suggests that HFS reduces large Aα and Aβ fiber activity to a greater extent than does traditional SCS at 50 kHz. They also found that traditional SCS affected C-fiber activity to a greater extent than did HFS [5] . Furthermore, kilohertz-level SCS induced pain inhibition at lower amplitudes of stimulation with earlier onsets.…”
mentioning
confidence: 99%
“…In a rat sciatic nerve ligation model both frequencies (1 kHz and 10 kHz) were effective, but the higher frequency was more effective in terms of onset of effect and its magnitude [9]. Clinical experience, however, showed that 5-kHz stimulation did not result in desired effects [13], whereas 10-kHz stimulation does relieve pain, but only at a very specific position of electrode contacts [11,12].…”
Section: New Stimulation Paradigmsmentioning
confidence: 89%
“…One suggestion, for example, was to replace conventional synchronous stimulation with a stochastic pattern in the hope that such irregular stimuli will be more effective in suppressing signal transmission in the central nervous system and perhaps prevent development of tolerance to stimulation [9]. It appears that the use of stochastic stimulation pattern so far has not been tested in laboratory or clinical settings.…”
Section: New Stimulation Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation